Digitalização bancária, fraude e população vulnerável: pesquisa realizada nos processos distribuídos nos anos de 2014 e 2023 na 5ª vara cível da comarca de Santo André/TJSP - Figueira, Adriana Bertoni Holmo (2024)
Since the advent of the digitalization of banking services, the exacerbated vulnerability of consumers lacking technological knowledge, combined with advanced age and low educational levels, places them in a subordinate position against large corporations. Alongside studies on responsible credit, consumer harassment, and overindebtedness, many consumers claim to be victims of fraud, being caught off guard by transactions they did not authorize or by criminals who, possessing sensitive data, impersonate financial institutions and mislead them. This empirical study analyzes the legal claims made by consumers in the years 2014 and 2023 with the element of "fraud" to compare the impact of the paradigm shift towards digital credit and identify the characteristics of this group before and after digitization. Utilizing a mixed-methods approach with quantitative and qualitative data analysis from a civil court in the São Paulo State Court of Justice, the study reveals that social and digital exclusion contributes to the increase in fraud against hyper-vulnerable consumers. The results may guide public policies aimed at digita